Case Report: Nonverbal approaches in the treatment of a patient with fibromyalgia with anger rooted in adverse childhood experiences - Adachi, Yuri; Hosoi, Masako; Nishihara, Tomoe; Hirabayashi, Naoki; Sawa, Takako; Matsushita, Tomoko; Tatsushima, Keita; Anno, Kozo; Tomioka, Mitsunao; Sudo, Nobuyuki (Frontiers in Pain Research, 2024)
In psychotherapy, it is important to establish and deepen a therapeutic trusting relationship, but patients who have experienced extreme adversity in childhood tend to have difficulty in building such a relationship. This paper reports a case of fibromyalgia with adverse childhood experiences (ACEs) in which a nonverbal approach was successful in building a trusting relationship.The patient is a woman in her late 40s. She had strong anger rooted in ACEs, including neglect by her father, a feeling of unfair parenting by her mother compared to her younger brother, overcontrol of her life by her mother, and sexual abuse by her uncle. She was filled with strong interpersonal distrust and anger, and the experience of an unsuccessful surgery compounded her distrust of medical care. The therapist initially had severe difficulty in verbal interaction with the patient. When conducting "drawing" therapy, she ignored the therapist's comments and completely blacked out the drawing paper. However, the patient-therapist relationship gradually changed, and verbal interaction became possible through the use of nonverbal approaches such as framing her drawing paper and "Towel Baby Holding."The therapist was able to understand the patient's emotions through these nonverbal approaches and to communicate with the patient that she understood her feelings. This approach was also successful in the patient's understanding of her own pathology. The patient became able to honestly express her feelings in words, which eventually enabled her to be introduced to mindfulness therapy, leading to a favorable treatment course.For patients with ACEs, a nonverbal approach helps build a therapeutic relationship and plays an important role in understanding the patient.